Economic transformation in Africa: Patterns, drivers, and implications for future growth strategies - Badiane, Ousmane; McMillan, Margaret S. (International Food Policy Research Institute, 2015)
This chapter takes a comprehensive look at the process of structural transformation among African countries, highlights the major shift that has taken place in the quality of structural change in the last decade, and examines in depth changes in the productivity of and employment within different economic sectors and their implications for future growth. An important part of this analysis addresses the emerging place and role in future growth processes of the informal goods and services sector, which is now the largest economic sector in most African countries, in addition to the agriculture and manufacturing sectors, which have been the focus of traditional growth theory.